Evaluation of the Surabaya Single Window (SSW) Alfa Program at the Public Service Center (SPP) Menur, Surabaya City - Rizki Kurniawan; Tauran T; Tjitjik Rahaju; Indah Prabawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Digital transformation in public services is a local government strategy to improve the effectiveness, efficiency, and transparency of services. The Surabaya City Government implemented the Surabaya Single Window (SSW) Alfa as an integrated electronic-based licensing and non-licensing service system. This study aims to evaluate the implementation of the SSW Alfa Program at the Menur Public Service Center (SPP) in Surabaya City. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. Research informants consisted of the Head of SPP Menur, service officers, and community users of SSW Alfa services. The program evaluation analysis used William N. Dunn's policy evaluation criteria, including effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results showed that from the aspects of effectiveness and efficiency, SSW Alfa was able to accelerate the licensing process and save time and service costs. However, from the aspects of adequacy and equity, the program has not fully reached all community needs, especially related to digital literacy and service access. In terms of responsiveness, services are still not optimal due to slow responses to public complaints. Meanwhile, from the aspect of accuracy, SSW Alfa is considered to be in line with community needs and the direction of Surabaya City's e-government policy. This study recommends improving public digital literacy, enhancing officer responsiveness, and enhancing the system so that all services can be accessed digitally without the applicant's physical presence.Â